Fermentable Fibers Enhance Aspects of Innate and Adaptive Immunity in Piglets infected with Salmonella Typhimurium - Correa-Matos, Nancy J.; Donovan, Sharon M.; Tappenden, Kelly A. (Puerto Rico Health Sciences Journal, 2020)
Objective: To test the hypothesis that fermentable fiber prevents Salmonella typhimurium infection-associated symptoms by enhancing innate and adaptive immune system in neonatal pigs. Methods: Two-d-old piglets (n=120) were randomized to receive either a nutritionally complete sow milk replacer formula (CON), or supplemented with methylcellulose (MCEL-non-fermentable), soy polysaccharides (SPS-moderately fermentable), or fructooligosaccharides (FOS-highly fermentable). On d7, piglets received an oral gavage of S. typhimurium-798, and continued receiving the same diets up to 48h post-infection. Ileal mucosal samples were obtained for further analyses. Results: A reduction in chloride secretion was observed in FOS when compared to other diets (p<0.0003). The number of ileal sulfo-acidomucins was higher (p<0.05) in FOS before infection compared with other diets. NFkB was inhibited in FOS followinginfection (p<0.05), when compared with CON. IL-1β expression was increased at 4h post-infection (p<0.05) in CON; however, this response was attenuated in the fiber groups. IL-6 expression was higher (p<0.05) in CON post- infection, higher in SPS at 24h (p<0.05), but unchanged in MCEL and FOS when compared to pre-infection values. FOS had a higher expression of neutrophil-chemoattractant IL-8 before infection (p<0.05) compared to other groups. Conclusion: The reduction in chloride secretion, proinflammatory cytokines expression and NFkB activation, and increased number of sulfo-acidomucins, and IL-8 expression in the fiber groups, indicates that the degree of fermentability impacts the innate and adaptive immune system, and could be the mechanisms by which dietary fibers reduce S. typhimurium infection-associated-symptoms in neonatal pigs and apply these results to infants.